Theory and practice of experience pedagogy - Danner, Stefan (Socialinė teorija, empirija, politika ir praktika, 2006)
The outcomes of experience pedagogy are analysed in the paper. The possible outcomes of experience pedagogy are defined in the first part. The role of the teacher is discussed in the second part. The author states the weave between plan and improvisation in the pedagogical process. In order to deal with not foreseen and unseen outcomes, it is effective to use the reflective improvisation methods. The reflective improvisation method is described in the last part of the paper.
Keywords: Experience pedagogy; Outcomes of teaching; Methods of reflective